Transmisi Budaya Orkes Gambus sebagai Praktik Pendidikan Musik Berbasis Komunitas di Desa Giham Balak, Lampung Barat - Latifah Islmulyani; Riyan Hidayatullah (Grenek: Jurnal Seni Musik, 2026)
This This study aims to analyze the role of the Akkon Jejama Group Gambus Orchestra as a form of community-based music education in Giham Balak Village, West Lampung. The focus of the research includes the learning system, the process of knowledge transmission, the role of the community, and the educational values ​​contained in musical activities. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study indicate that the learning process in the community takes place informally through direct practice, imitation methods, and interactions between senior players and the younger generation. The community acts as an open and inclusive learning environment, thus supporting the natural development of members' musical abilities. In addition, the existence of the Akkon Jejama Group Gambus Orchestra also contributes to the preservation of local culture through the ongoing involvement of the younger generation. This study contributes to the study of community-based music education by demonstrating that traditional arts communities can function as effective learning spaces and as a means of preserving local culture. Thus, community-based music education in this group serves as an alternative learning model that supports the development of musical skills, strengthening social values, and the sustainability of traditional arts.